2021
DOI: 10.1021/jacs.1c08851
|View full text |Cite
|
Sign up to set email alerts
|

Stable Dendrite-Free Sodium–Sulfur Batteries Enabled by a Localized High-Concentration Electrolyte

Abstract: Ambient-temperature sodium–sulfur batteries are an appealing, sustainable, and low-cost alternative to lithium-ion batteries due to their high material abundance and specific energy of 1274 W h kg–1. However, their viability is hampered by Na polysulfide (NaPS) shuttling, Na loss due to side reactions with the electrolyte, and dendrite formation. Here, we demonstrate that a solid–electrolyte interphase rich in inorganic components can be realized at both the sulfur cathode and the Na anode by tweaking the solv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
63
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 105 publications
(75 citation statements)
references
References 39 publications
1
63
2
Order By: Relevance
“…It can be seen that besides physical Reproduced with permission. [21,30,[46][47][48][49][50] Copyright 2016-2021, Wiley-VCH, Springer Nature, and American Chemical Society.…”
Section: Catalytic Reversible Conversion Of Polysulfidesmentioning
confidence: 99%
See 4 more Smart Citations
“…It can be seen that besides physical Reproduced with permission. [21,30,[46][47][48][49][50] Copyright 2016-2021, Wiley-VCH, Springer Nature, and American Chemical Society.…”
Section: Catalytic Reversible Conversion Of Polysulfidesmentioning
confidence: 99%
“…Furthermore, based on the research progress in the LiS battery system, Manthiram and co‐workers demonstrated that the quasi‐solid state conversion pathway of sulfur could be realized by tweaking the solvation structure of the electrolyte, and the challenges at both electrodes can be addressed simultaneously (NaPSs shuttling and facilitating dendrite‐free Na‐metal plating and stripping) in NaS batteries. [ 50 ] Herein, it demonstrated that a unique solventized structure was formed with the dimethoxyethane to sodium bis(fluorosulfonyl)imide (DME:NaFSI) molar ratio decreases. Then, galvanostatic charge–discharge test was employed to analyze the conversion pathway of sulfur electrodes in localized high concentration electrolytes (LHCE) (Figure 10i).…”
Section: Catalytic Reversible Conversion Of Polysulfidesmentioning
confidence: 99%
See 3 more Smart Citations